2013
DOI: 10.1056/nejmoa1212115
|View full text |Cite|
|
Sign up to set email alerts
|

Mutations in COQ2 in Familial and Sporadic Multiple-System Atrophy

Abstract: Functionally impaired variants of COQ2 were associated with an increased risk of multiple-system atrophy in multiplex families and patients with sporadic disease, providing evidence of a role of impaired COQ2 activities in the pathogenesis of this disease. (Funded by the Japan Society for the Promotion of Science and others.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
161
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(166 citation statements)
references
References 35 publications
3
161
2
Order By: Relevance
“…We analyzed the SCA1 , SCA2 , SCA3 , SCA6 , SCA7 , SCA8 , SCA12 , SCA17 , SCA31 , DRPLA , and COQ2 genes in all patients with MSA-C and in a part of patients with SCA3 [1,16]. The remaining part of patients with SCA3 had been genetically diagnosed in other hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed the SCA1 , SCA2 , SCA3 , SCA6 , SCA7 , SCA8 , SCA12 , SCA17 , SCA31 , DRPLA , and COQ2 genes in all patients with MSA-C and in a part of patients with SCA3 [1,16]. The remaining part of patients with SCA3 had been genetically diagnosed in other hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…We also performed Southern blot analysis at Columbia University research laboratory to determine the size of hexanucleotide repeat expansions of C9orf72 and found that both the proband and her brother had repeats of more than 1000 with similar expansion size. In addition, we also excluded the COQ2 sequence variant V343A associated with MSA 12 and the pathological repeat expansions of SCA36 13 in the proband.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that abnormal mitochondrial accumulation, as well as fission, possibly precedes GCI formation. The Multiple System Atrophy Research Consortium reported that functionally impairing nucleotide variants in COQ2 , which encodes the protein coenzyme Q 2 that is essential for the biosynthesis of coenzyme Q 10 , were associated with an increased risk of MSA in multiplex families and in about 10% of sporadic MSA cases [23]. Patients with defective COQ2 mutations were shown to have GCI-positive oligodendroglia [23], providing direct evidence for a role of mitochondrial dysfunction in MSA pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We studied patients with sporadic MSA (Cases 1–10, 12–14), familial MSA (Case 11), who was already reported as homozygously carrying the M128V-V393A COQ2 mutation [22,23], normal controls who died from non-neurological conditions (Cases 15–26), and disease controls including ALS (Cases 27 and 28), oligodendroglioma (Cases 29 and 30), MS (Cases 31–34) and others (Cases 35–37) (Table 1). The Case 11 as well as her/his sibling were both clinically diagnosed as MSA-P, pathologically confirmed as MSA (22), and whole genome sequence analysis on them lead to an identification of COQ2 mutations in MSA (23).One of these two sibs, the only available sample upon investigation, were confirmed to show a significantly reduced intracellular coenzyme Q10 level in her/his brain tissue, suggesting a functional consequence of this mutation (23).…”
Section: Methodsmentioning
confidence: 99%